PENGARUH KETERTINGGALAN AKSES INFORMASI TERHADAP PEMBANGUNAN DI DAERAH PERBATASAN ANTARA INDONESIA DAN MALAYSIA - Arman, Yohanes; Supadi, Fransiska Nyoman; Geong, Mario Pietro Kurniawan; Pramana, Hanif Al Faiq; Yazakur, Patrick Aleksandro Reinaldo (Gapenas Publisher, 2025)
This study investigates the impact of limited information access on development in border regions between Indonesia and Malaysia. Employing a qualitative research method with a literature review approach, the study analyzes the correlation between information access and various development indicators. Findings reveal a strong negative correlation between limited information access and key development indicators, including the Human Development Index (HDI), economic development, community participation, human resource quality, and disaster preparedness. The limited access creates a cycle of poverty and backwardness, exacerbated by factors such as poverty, inequality, weak governance, and geographical isolation. The study emphasizes the crucial need for comprehensive strategies to improve information access and digital literacy to foster sustainable and inclusive development in these border regions.